Promising therapeutic approaches using CRISPR/Cas9 genome editing technology in the treatment of Duchenne muscular dystrophy - Hasan Mollanoori; Yazdan Rahmati; Bita Hassani; Meysam Havasi Mehr; Shahram Teimourian (Genes and Diseases, 2021)
Duchenne muscular dystrophy is an X-linked recessive hereditary monogenic disorder caused by inability to produce dystrophin protein. In most patients, the expression of dystrophin lost due to disrupting mutations in open reading frame. Despite the efforts in a large number of different therapeutic approaches to date, the treatments available for DMD remain mitigative and supportive to improve the symptoms of the disease, rather than to be curative. The advent of CRISPR/Cas9 technology has revolutionized genome editing scope and considered as pioneer in effective genomic engineering. Deletions or excisions of intragenic DNA by CRISPR as well as a similar strategy with exon skipping at the DNA level induced by antisense oligonucleotides, are new and promising approaches in correcting DMD gene, which restore the expression of a truncated but functional dystrophin protein. Also, CRISPR/Cas9 technology can be used to treat DMD by removing duplicated exons, precise correction of causative mutation by HDR-based pathway and inducing the expression of compensatory proteins such as utrophin. In this study, we briefly explained the molecular genetics of DMD and a historical overview of DMD gene therapy. We in particular focused on CRISPR/Cas9-mediated therapeutic approaches that used to treat DMD.